HUBUNGAN KOHESIVITAS DENGAN DINAMIKA KELOMPOK DALAM BIMBINGAN KELOMPOK PADA SISWA SMP NEGERI 13 SEMARANG - Herlianto, Purwo (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
In the student group activities specifically in this case the group guidance requires mutual happiness, mutual dependence, and the encouragement to hold out in the group what we might call as a group cohesiveness. Cohesiveness is important to grow of group dynamics to achieving the goals. Therefore, in this research aimed to determine distant of the relationship between the cohesiveness and the dynamicsof the group. This research is belonging to ex post facto research , using non-test methods in data collection. The instrument using a scale to determine the level of cohesiveness and level of group dynamics, as well as an interview instrument to supported data collection. The results of this research showed a strong relationship between the group of cohesiveness and group dynamics in the group  guidance process in the students of SMP Negeri 13 Semarang, with correlational value r = 0.702, with a significance level of p = 0.000 <? = 0.05.